MARKETING STRATEGY AT RANCABUAYA BEACH USING THE ANALYSIS FACTORS OF EXPANDED MARKETING MIX AND PROMOTION MIX - Teguh Iman Basuki (STIE Binaniaga, 2018)
West Java is one of the provinces in Indonesia that has strong potential and wisdom, mountains range from the east to the west of the Bogor Peak area, as well as the southern region which has attractive coastal views and panoramas from Pangandaran district to sukabumi district. One of the southern parts of West Java which has the potential of coastal tourism is Garut regency, one of them is the Rancabuaya beach, the potential of Rancabuaya beach tourism is now being developed to attract tourists, located in Purbayani village in Caringin sub-district with an area of 10 hectares while the current area used as a new tourism area of 2 hectares, which is also directly adjacent to the Indian Ocean with the characteristics of having big tide and large rocks and rock cliffs that are quite high, another potential tourism attraction is the presence of a waterfall directly facing the beach. However, Rancabuaya beach is very beautiful, but the level of tourist visits is less than the total visitors to other southern Jabar (west Java) beach attractions, which is Pangandaran beach. Visitors to rancabuaya beach are very crowded only in certain events such as, New year, Eid or other National holiday. This study aims to find out what the right marketing model can be applied at Rancabuaya beach tourism area. The results of this study indicate that the indicators of income mix and promotion mix get a good response from the respondents and have a strong relationship to the factors that are formed. Keywords: Rancabuaya beach, promotion, marketing